2021
DOI: 10.1038/s41598-021-96008-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting ROS/NF-κB signaling pathway by the seedless black Vitis vinifera polyphenols in CCl4-intoxicated kidney, lung, brain, and spleen in rats

Abstract: Carbon tetrachloride (CCl4) is an abundant environmental pollutant that can generate free radicals and induce oxidative stress in different human and animal organs like the kidney, lung, brain, and spleen, causing toxicity. The present study evaluated the alleviative mechanism of the isolated polyphenolic fraction from seedless (pulp and skin) black Vitis vinifera (VVPF) on systemic oxidative and necroinflammatory stress in CCl4-intoxicated rats. Here, we found that the administration of VVPF to CCl4-intoxicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Further lipid peroxidation was raised because of covalent binding of CCL4 metabolites, CCL3• and CCL3OO•, to the protein in the liver cell causing destructive effects (Abbasi et al, 2021). In addition, hepatic GSH content was depleted after CCL4 administration which might be due to the extreme need of GSH to eradicate the CCL3OO• radicals and hypochlorous acid, where GSH is the key mediator in detoxification process inside the body (Habashy et al, 2021). This result corroborates with the reports of (Emmanuel et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Further lipid peroxidation was raised because of covalent binding of CCL4 metabolites, CCL3• and CCL3OO•, to the protein in the liver cell causing destructive effects (Abbasi et al, 2021). In addition, hepatic GSH content was depleted after CCL4 administration which might be due to the extreme need of GSH to eradicate the CCL3OO• radicals and hypochlorous acid, where GSH is the key mediator in detoxification process inside the body (Habashy et al, 2021). This result corroborates with the reports of (Emmanuel et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…In addition to Ccl4’s significant hepatotoxicity, some damage was recorded in other organs, with the mechanism virtually linked to its increase in lipid peroxidation and free radicals. Similar phenomena were observed in this investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress can impede wound healing ( 19 , 47 ). The results of extensive studies showed that pretreatment of keratinocytes (mouse skin) with H significantly reduced radiation-induced oxidative stress ( 48 ), lipid peroxidation, while increasing the expression levels of antioxidant enzymes ( 20 , 49 ).…”
Section: Discussionmentioning
confidence: 99%